2013
DOI: 10.1177/1934578x1300800103
|View full text |Cite
|
Sign up to set email alerts
|

Some Secrets of Argania spinosa Water Economy in a Semiarid Climate

Abstract: Argania spinosa is an example of an avoider tree growing under semi-arid conditions in Morocco. To assess what are the physiological strategies of this species, different variables were measured through an annual cycle in two populations located in the species' main distribution area. Results show the expected decrease of leaf water potential (Ψ) with an increase of water-use efficiency (A/g s) with the onset of the dry season. In summer, leaf conductance (g s) was sensitive to vapour pressure deficit (VPD), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…These qualitative relationships are in accord with the results reported between Ψ b and g s in other species (Gomes et al 2004;Wahbi et al 2005;Grzesiak et al 2013). Furthermore, Diaz Barradas et al (2013) have highlighted a significant relationship between VPD and stomatal conductance in A. spinosa in a summer day, suggesting that the stomata are responsive to VPD. In fact, the sensitivity of stomata to reduced leaf water potential varies widely depending on the species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These qualitative relationships are in accord with the results reported between Ψ b and g s in other species (Gomes et al 2004;Wahbi et al 2005;Grzesiak et al 2013). Furthermore, Diaz Barradas et al (2013) have highlighted a significant relationship between VPD and stomatal conductance in A. spinosa in a summer day, suggesting that the stomata are responsive to VPD. In fact, the sensitivity of stomata to reduced leaf water potential varies widely depending on the species.…”
Section: Discussionmentioning
confidence: 99%
“…A. spinosa proved to tolerate drought stress by effectively controlling water loss mainly through stomatal closure and improving water use efficiency (Diaz Barradas et al 2010Chakhchar et al 2015bChakhchar et al , 2015c. Diaz Barradas et al (2013) also reported that the leaf conductance response of A. spinosa to drought environment seems to depend on the variation of vapour pressure deficit (VPD). In fact, plants of A. spinosa adapt to drought by down-regulation of several physiological/biochemical processes, thereby maintaining growth even under severe drought stress (Chakhchar et al 2015a(Chakhchar et al , 2015b(Chakhchar et al , 2015c.…”
Section: Introductionmentioning
confidence: 99%
“…There are comparatively few studies that investigate the photosynthetic and stomatal responses of the argan tree to drought. Previous studies have indicated differences in the leaf water potential, antioxidant activity ( Diaz-Barradas et al, 2010 ; Chakhchar et al, 2015 , 2016 ), leaf morphology ( Diaz Barradas et al, 2013 ; Chakhchar et al, 2015 ) and chlorophyll fluorescence parameters ( Diaz-Barradas et al, 2010 ) response to drought of argan trees collected from different habitats. Despite the restricted range of the argan tree (950,000 ha: Lefhaili, 2010 ), genetic analyses have indicated variation between accessions collected from different habitats (hereafter referred to as ecotypes; El Bahloul et al, 2014 ) that may underpin this variety of response to water deficit.…”
Section: Introductionmentioning
confidence: 99%
“…Despite occupying the habitat with the greatest mean annual precipitation, the argan trees from the mountainous habitat exhibited the largest reduction in leaf water potential during the summer, corresponding to the lowest P N values and quantum efficiency of CO 2 assimilation of the three ecotypes ( Diaz-Barradas et al, 2010 ). The argan trees growing under natural conditions showed close co-ordination of stomatal conductance ( G s ) with leaf to air vapor pressure deficit (VPD; Diaz Barradas et al, 2013 ) and leaf water potential ( Diaz-Barradas et al, 2010 ). This suggests that the physiological and gas exchange responses of argan trees are highly adapted to growth in a habitat characterized by high evaporative demand and low water availability.…”
Section: Introductionmentioning
confidence: 99%
“…Díaz Barradas et al (2013) evidence that this tree species is able to maintain an elevated productivity even in the dry season, by a high assimilating rate of carbon during the early hours of the day. Accordingly, it seems obvious that argan trees are adapted to arid conditions and to an irregular precipitation regime (severe water stress, high radiation and hot temperatures).…”
Section: Introductionmentioning
confidence: 99%